Assessing the relationship between principals' transformational and transactional leadership styles on motivation among secondary school teachers in Jasin district, Melaka / Nurul Fatinah Dellah - Dellah, Nurul Fatinah (2015)
Teaching is a very challenging profession, no less due to heavy duties and responsibilities. It is very challenging because teachers not only teach, but also have to deal with the problem of unruly students and clerical work that requires a lot of time to complete. Some of the reforms in education system like Secondary School Curriculum Standard (KSSM), the Primary School Standard Curriculum (KSSR) and School Based Assessment have caused the teachers strain. These situations have demotivated the teachers to perform the best duties as an educator. Hence, it is important to identify the factors that could enhance teacher motivation to school. The purpose of this study was to examine the influence of perceived principals' leadership styleson motivation. A sample of 278 teachers from secondary schools in Jasin District was participated in this study. They were selected based on cluster random sampling. Descriptive and inferential statistics were used to analyse data that was collected using the survey method. Based on the data collected, the findings showed that generally secondary school teachers in the Jasin district have revealed moderate motivation level and perceived their principals demonstrated moderate transformational and transactional leadership styles.The findings also revealed that there was a significantly positive and moderate linear relationship between transformational leadership style and motivation.Besides, relationship between transactional leadership style and motivation also showed a significantly positive and moderate linear relationship. Leadership styles, transformational and transactional, were significant predictors of motivation.In term of determining the contributions of the significant predictors of motivation, the results revealed that transformational leadership styleand transactional leadership stylecontributed 21.0%to the variance of motivation. The findings of this study have implications to the role of principal in exercising transformational leadership and transactional leadership styles to increase teachers' motivation. Based on the findings, this study also provides recommendations for practices and future research.